Unilateral Option Arbitration clauses: An unequivocal choice for arbitration under the ECHR?. Issue 1 (February 2018) - Zelst, Bas van
Unilateral option arbitration clauses (UAC) are clauses under which the parties bound by it are restricted to bringing proceedings in a particular jurisdiction, while at the same time providing one or more parties the option to elect that a dispute be referred to arbitration. The latter right is unilateral in that it may only be invoked by the beneficiary party or parties that are designated in the UAC. This article submits that the concept of a UAC is compliant with the European Convention on Human Rights (ECHR). More particularly it argues that UACs meet the requirements – developed through the case law of the European Court of Human Rights (ECtHR) – that the waiver of the right to access to an impartial and independent court established by law is agreed upon freely and unequivocally. It is concluded that there is nothing in the ECtHR's case law to suggest that a UAC conferring the choice for arbitration or litigation only to the beneficiary of the UAC would be contrary to these requirements.